Trend Analysis of Research Funded by Defence Research and Development Organisation - Chandra, Ranadip (Journal of Information and Knowledge, 2022)
This study was carried out to investigate the trend of research funded by Defence Research and Development Organisation (DRDO) published between 2014 to 2018. Total 1569 articles published in 701 sources with an average 9.04 citations per document were found in Scopus database and downloaded in the BibTeX file format. Bibliometrix R Package was used to analyze different aspects of research. The study involved 3576 authors with 0.44 documents per author and 2.28 authors per document. The top 10 productive journals published 823 articles (52.45%). The journal RSC Advances published the highest number of articles. The top 10 productive authors published a total of 445 articles with 3836 received citations. Defence Metallurgical Research Laboratory collaborated with the highest number of research. Majority of the researches were carried out in India with collaboration with other countries, mainly from developed countries. The majority of the research was carried out under the subject microstructure, mechanical properties, X ray diffraction, optical properties, hypoxia, etc. This work may help DRDO to evaluate their criteria in funding research in future.